Nutritional monitoring of patients post‐bariatric surgery: implications for smartphone applications. Issue 1 (10th July 2017) - Elvin‐Walsh, L.; Ferguson, M.; Collins, P. F.
Abstract: Background: Optimal results from bariatric surgery are contingent on patient commitment to dietary and lifestyle changes and follow‐up care. The present study aimed to investigate the attitudes and use of mobile health (mHealth) smartphone applications (apps) as a potential tool for maintaining connectivity between dietitians and patients post‐bariatric surgery. Methods: A cross‐sectional online survey was developed and distributed to a purposeful sample of bariatric dietitians and bariatric patients in Australia. The survey questions explored technology penetration (smartphone and app use), communication preferences, nutrition monitoring methods, professional relationship expectations and reasons for loss to follow‐up. Results: Survey completion rate was 85% ( n = 50/59) for dietitians and 80% ( n = 39/49) for patients. Smartphone ownership was 98% and 95% for dietitians and patients, respectively. Common reasons given for losing patients to follow‐up suggest that a traditional in‐clinic practice setting could be a barrier for some. Most dietitians ( n = 48; 91%) prefer to see patients face‐to‐face in their clinic, whereas patient preferences extended to e‐mail and mobile messaging. Sixty‐eight percent of bariatric patients were receptive to two‐way communication with dietitians via an app between clinic visits. Both cohorts recognised the potential for emerging technologies to be used in practice, although there was no single routinely recommended mHealth app. Conclusions: The present study provides the first insight into the use of mobile devices and apps by post‐bariatric patients and the dietitians who support them. A mixture of traditional methods and smartphone technology is desirable to both dietitians and patients. The utility and effectiveness of such technologies should be confirmed in future intervention studies.